Avaliação do ambiente de prática profissional e sua relação com o clima de segurança e a síndrome de Burnout em profissionais de enfermagem de unidades de tratamento antineoplásico - Costa, Amanda de Fátima Alves (2022)
The nursing practice environment is defined as the presence of organizational peculiarities that collaborate or hinder the development of professional practice. These peculiarities include a management that supports nursing, with adequate dimensioning of human resources; nursing team with competence, autonomy and prepared to work with the health team. The objective was to evaluate the environment of professional nursing practice in anticancer treatment units and its implications for the safety climate and the team's Burnout domains. Cross-sectional and correlational study carried out between November 2019 and December 2021, in four institutions specializing in anticancer treatment in Fortaleza, Ceará. Four instruments were applied for data collection: Sociodemographic and Professional Questionnaire, Practice Environment Scale – Brazilian Version (PES), Maslach Burnout Inventory (IBM) and Safety Attitudes Questionnaire - Short Form 2006 – Brazilian version (SAQ). The sample was formed by convenience, totaling 59 nursing professionals. Data were processed using SPSS 20.0 software. Descriptive and inferential statistics were used, followed by bivariate analysis and multiple linear regression. In the bivariate analysis, the chi-square, likelihood ratio and Fisher's exact tests were used. To compare the SAQ means, according to sociodemographic/occupational variables, Student's t and ANOVA tests were applied. For correlation analysis between the three PES, SAQ and IBM scales, Spearman's r correlation coefficient was applied. The Structural Equation Modeling analysis was used to evaluate the relationships between the characteristics of the practice environment to identify the estimates of the direct and indirect effects of this environment on the safety climate and on the Burnout domains of the study participants. The research was approved by the research ethics committee (no4.244.467 e 4.853.123). As a result, we found a mostly female sample, with an average age of 37 years, experienced in the area, bond by CLT, with a workload of 47 hours per week. The professional practice environment (PES) was evaluated as favorable, with emphasis on collegial relationships between nurses and doctors (Subscale 5). In the perception of the safety climate, only the domains of Satisfaction at Work and Safe Behavior were positive. Participants had a low level of Burnout. The professional practice environment was positively correlated with Professional Achievement (r=0.337; p=0.009) and Safety Climate (SAQ) (r=0.511; p=0.000). Emotional exhaustion and safety climate had a negative correlation (r=-0.307; p=0.019). Only the ESP subscale 5 (collegiate relationships between physicians and nurses) was found to be influenced in the domains of emotional exhaustion and professional fulfillment of Burnout. The study made it possible to identify elements of the work environment in antineoplastic treatment units which are favorable to professional practice and the points of confrontation that can be changed that demand a careful analysis by nursing managers, in order to guarantee the development of quality care and safety.